Does masculine orientation affect entrepreneurial intentions? Empirical research results among students - Krystian Bigos; Jan Chlanda; Michał Ciepły; Natalia Ciosmak; Adam Michalik; Anita Pustułka (International Entrepreneurship Review, 2023)
Objective: The article aims to present the research results on the relationship between the national culture dimension of masculinity/femininity according to Hosfstede’s approach and declared entrepreneurial intentions.